ESSENCE OF FORGIVENESS AMONG THE SECONDARY SCHOOL STUDENTS FROM NAGAON TOWN OF ASSAM - Sarma, Mrigakshi (ShodhKosh: Journal of Visual and Performing Arts, 2024)
The statement of the present study is, “Essence of Forgiveness among the Secondary School Students from Nagaon Town of Assam.” Based on the problems of the study the objectives framed are: i) To find the difference in the dimension of forgiveness among the Secondary School Students from Nagaon Town of Assam. ii)To find the difference in the essence forgiveness among the Secondary School Student from Nagaon Town of Assam with regard to their Gender (Male/Female). In the present study Descriptive survey method is used as it aims to systematically and accurately describe a population and situation or phenomenon. Simple Random Sampling technique is used to collect the data from 400 samples. The result found that there is no significant difference between forgiveness among male and female of Secondary School Students from Nagaon Town of Assam.